When does human life begin? : an evolutionary perspective - Schwartz, Jeffrey H. (Array, 2009)
The question – »when does human life begin?« – is without doubt an important one, and the answer to it has different yet equally profound consequences in diverse fields such as medicine, theology, ethics, and anthropology. But before one can begin to tackle the topic and its ramifications, one must first be certain that that one is not conflating a conception about »the beginning of human life« with the biology relating to »the beginning of life«. Here I shall discuss these issues from the perspectives of the history and philosophy of science and evolutionary biology with the hope that this might shed light on the multifaceted and hierarchical nature of this typically highly charged subject.